Intelligent Mobile Robot Navigation - Cuesta, Federico; Ollero, Aníbal (Springer Tracts in Advanced Robotics, 2005)
Intelligent Mobile Robot Navigation builds upon the application of fuzzy logic to the area of intelligent control of mobile robots. Reactive, planned and teleoperated techniques are considered, leading to the development of novel fuzzy control systems for perception and navigation of nonholonomic autonomous vehicles. The unique feature of this monograph lies in its comprehensive treatment of the problem from the theoretical development of the various schemes down to the real-time implementation of algorithms on mobile robot prototypes. As such, the book spans across different domains ranging from mobile robots to intelligent transportation systems, from automatic control to artificial intelligence.